THE 2011 LANDING OF TURKEY ON SOMALIA: THE “STATE TO PEOPLE” ASPECT OF TURKISH FOREIGN POLICY TOWARDS SUB-SAHARAN AFRICA - Volkan İpek (European Scientific Journal, ESJ, 2014)
Although Turkey's relations with the African continent have had a long history, an unprecedented level of interaction is recently being observed between Turkey and Sub- Saharan Africa. Started by the growing importance of non-Western world in Turkish foreign policy apart from the 1990s, Sub-Saharan Africa became one of the regions where Turkey intensified its relations. The Africa Opening Plan that was prepared in 1998 has been the catalyzer of the Turkey’s foreign policy initiative towards Sub-Saharan Africa. Through comparing the plan’s initial objectives with the outcomes, we argue that the Turkey has successfully put the 1998 Plan into action. Behind this success was careful implementation of the cultural component of the plan, which helped to encourage not only state-to-state but also state-to-people and people-to-people relations. These two latter relations made Turkey’s foreign policy initiative in Sub-Saharan Africa both sustainable and equitable.